Numerical reconstruction of traumatic brain injury in skiing and snowboarding - Bailly, N.; Llari, M.; Donnadieu, T.; Masson, C.; Arnoux, P. J. (Medicine & Science in Sports & Exercise, 2018)
Purpose: Proper evaluation of ski helmet designs and safety standards should rely on head impact conditions involved in skiing and snowboarding head injuries. To study these impacts, main crash scenarios involving head injuries are numerically replicated.